2002
DOI: 10.1088/0960-1317/12/5/315
|View full text |Cite
|
Sign up to set email alerts
|

A low-temperature wafer bonding technique using patternable materials

Abstract: In this paper we present a silicon wafer bonding technique for 3D microstructures using MEMS process technology. Photo-definable material with patternable characteristics served as the bonding layer between the silicon wafers. A bonding process was developed and several types of photo-definable material were tested for bonding strength and pattern spatial resolution. The results indicated that SU-8 is the best material with a bonding strength of up to 213 kg cm−2 (20.6 MPa), and a spatial resolution of 10 μm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 22 publications
2
69
0
Order By: Relevance
“…Finally we used thermal bonding to bond the two chips firmly and seal the chambers around the side wall, leaving only the conduction channels and electrolyte injection channels open. We tried two kinds of bonding method using either parylene or photoresist (Pan et al 2002). Based on the experimental data for diaphragm deflection, calculation shows that the photoresist bonding can hold under pressures as high as 500 psi (3.45 × 10 6 Pa).…”
Section: Fabrication Resultsmentioning
confidence: 99%
“…Finally we used thermal bonding to bond the two chips firmly and seal the chambers around the side wall, leaving only the conduction channels and electrolyte injection channels open. We tried two kinds of bonding method using either parylene or photoresist (Pan et al 2002). Based on the experimental data for diaphragm deflection, calculation shows that the photoresist bonding can hold under pressures as high as 500 psi (3.45 × 10 6 Pa).…”
Section: Fabrication Resultsmentioning
confidence: 99%
“…Since a layer of polymer or inorganic adhesive is always spun before bonding, it is very suitable for non-uniform surfaces and for bonding at low temperature. Benzocyclobutene (BCB) and SU-8 are the most common materials used in 3D integration, since high bonding strength can be easily achieved with these two polymer materials (Niklaus et al, 2001;Pan et al, 2002).…”
Section: Overview On Bonding Technologies In 3d Integrationmentioning
confidence: 99%
“…It is reported that a bonding strenght of ∼20 MPa can be achieved if SU-8 is used as intermediate layer for adhesive wafer bonding [8]. Wafer bonding with SU-8 can be performed simply by applying contact force and heat to a stack of wafers which carry SU-8 structures [9].…”
Section: Adhesive Wafer Bonding With Su-8mentioning
confidence: 99%